"He too will become a nation and he too will become great": The information needs of the "Bnei Menashe" immigrant community in Israel as capability. (June 2020) - Shomron, Baruch; Schejter, Amit
The "Bnei Menashe" are a marginalized community that immigrated from India to Israel. The community has diverse information needs, yet they are characterized by difficulties that prevent them from acquiring vital information. In this study, we utilized Sen's (1993) "capabilities approach" as well as Friedland et al. (2012) "critical information needs" for the identification of the Bnei Menashe's information capabilities, and the ways in which they answer them. The study was conducted using semi-structured individual in-depth interviews. The findings of the study relate that the Bnei Menashe succeed only partially in realizing the capability of being informed. This is a result of the partial technological exclusion that characterizes the community. This is a first-of-its-kind study, as the Bnei Menashe have not been studied methodically. Furthermore, the utilization of the capabilities approach represents a major contribution to existing communication theories, as the approach allows for a more wholesome understanding of the role of information and communication technologies in society.